Theoretical modelling of interdigitated electrode sensor for mammalian cell characterization - Mohd Mansor, Ahmad Fairuzabadi; Nordin, Anis Nurashikin (Institute of Electrical and Electronics Engineers Inc., 2018)
Interdigitated Electrodes (IDEs) have been widely used in biological cellular characterization such as the Electrical Cell-Substrate Impedance Sensing (ECIS). Optimization of IDEs are crucial to obtain high accuracy of measurement that associates with the biological cell activities. However, not much research studies the generation of electric field by the IDEs geometry especially in cellular application. In this work, theoretical modelling of IDEs was done by modelling the IDEs equivalent circuit consisting of 3 major components; double layer capacitance, CDL, solution capacitance, CSOL and solution resistance, RSOL. Simulation using MATLAB and COMSOL Multiphysics was done to study the effect of geometrical parameters (width of electrodes (W), spacing between electrodes (S) and total number of electrodes (N)) on the cut-off frequency (FLOW), solution resistance (RSOL) and the average electric field magnitude based on the equivalent circuit model. The simulation results show three main findings; lowest FLOW to be at the ratio of a=0.54 and N16, lowest RSOL at smaller a and higher N, and saturated electric field at N18. The results suggested that the optimal configuration of IDEs with a fixed length of electrode of 7000μm is to have the ratio of (S/W) as 0.54 and N as 18.